Identification of seminal proteins related to the inhibition of mate searching in female crickets. (19th October 2020) - Moschilla, Joe A; Tomkins, Joseph L; Simmons, Leigh W
Abstract: In response to the reduction in fitness associated with sperm competition, males are expected to evolve tactics that hinder female remating. For example, females often display a postmating reduction in their sexual receptivity that has been shown to be mediated by proteins contained in a male's seminal fluid (sfps). However, although there has been comprehensive research on sfps in genetically well-characterized species, few nonmodel species have been studied in such detail. We initially confirm that female Australian field crickets, Teleogryllus oceanicus, do display a significant reduction in their mate-searching behavior 24 h after mating. This effect was still apparent 3 days after mating but was entirely absent after 1 week. We then attempted to identify the sfps that might play a role in inducing this behavioral response. We identified two proteins, ToSfp022 and ToSfp011, that were associated with the alteration in female postmating behavior. The knockdown of both proteins resulted in mated females that displayed a significant increase in their mate-searching behaviors compared with females mated to males having the full compliment of seminal fluid proteins in their ejaculate. Our results indicate that the female refractory period in T. oceanicus likely reflects a sperm competition avoidance tactic by males, achieved through the action of male seminal fluid proteins. Abstract : Male field crickets transfer seminal fluid proteins in their ejaculate that reduce the risk of sperm competition by inhibiting female mate-searching behavior. Females are less sexually receptive after mating and are therefore less likely to mate with additional males. We show that this behavioral response is established 1 day after mating, lasts for less than a week and is at least partly mediated by two proteins transferred in the seminal fluid component of the ejaculate.